Requerimientos del campo ocupacional local regional y Nacional en relación a la oferta formativa de la Carrera de Enfermería de la Universidad Estatal de Bolívar años 2020-2021 - Sánchez Yánez, Julissa Alexandra (2022)
Nursing practice must meet certain requirements, some related to the Law of professional practice and others directly related to the functions of care activities, based on this, the objective of this research was proposed: Establish what are the requirements of the occupational field local, regional and national in relation to the educational offer of the Nursing Career of the State University of Bolívar, period 2020 - 2021. Using as a methodology the quantitative descriptive approach, using the survey as an instrument to collect the information, which was applied to 131 nursing professionals and 28 employers using Google forms as a tool and subsequently performing a numerical statistical analysis that allowed us to know the generalized trends and opinions of graduates regarding the relevance of the training offer of the Nursing Career and the needs and requirements current It is from the occupational field. The results of the surveys applied to employers and graduates showed that the requirements of the occupational field focus on the ability to offer comprehensive and humanistic care based on the cognitive abilities and skills acquired during training, in addition to the ability to develop and execute protocols nursing care and health promotion programs, in addition to the fact that professionals must have the skills to develop and execute nursing care procedures and protocols. In a particular way with regard to the professionals of the Nursing Career of the Bolívar State University, the employers detected the need to reinforce knowledge in different health services to satisfy their requirements, the main ones being family and community nursing, intensive care units, nursing and emergency administration. Concluding The relevance of the educational offer of the nursing career at the Bolívar State University for the year 2020 - 2021 was updated, based on the articulation of the data collected on the current health situation of the Bolívar province, the preferences of the 3rd Baccalaureate students compared to the preferences about third level studies, the current characteristics of the occupational field according to the graduates of the Nursing Career and the requirements of the employers of different Zonal Coordination’s in Health. Keywords: Requirements,